Penentu Struktur Modal: Bukti dari Perusahaan Syariah di Indonesia - Habibur Rachman Nur (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2020)
Abstract: Capital structure decisions are one of the most important issues in financial management that can contribute to maximizing corporate value. Likewise, capital structure decisions affect capital costs and capital budgeting decisions. The purpose of this study is to examine the effect of selected variables on leverage in accordance with the empirical investigation of Özde Öztekin, most determinants of companies, industries, and macroeconomics are company size, tangibility, industrial leverage, profit, and inflation that connect structure theory capital based on corporate financing in sharia companies in Indonesia using multiple regression analysis. Samples used from companies that consistently registered in the Jakarta Islamic Index (JII) during the period 2016 to 2018 were 18 companies. The results show that industrial leverage variable has a significant positive relationship with leverage in accordance with the trade off theory, the greater the industry leverage, the higher the debt financing. And there is a significant inverse relationship between earnings and leverage based on the pecking order theory, the more profits a company gets the less debt it uses Keywords: Capital structure, Sharia Companies, Jakarta Islamic Index, Indonesia.